«Fornøielig uden Skjenden, Hug og Slag» Abc- og lesebokforfatteren Hans Jacob Grøgaard – en pioner i sin tid - Berit Eide Johnsen (Heimen)
The ABC and schoolbook author Hans Jacob Grøgaard – a pioneer of his time In 2014, the parish pastor Hans Jacob Grøgaard (1764–1836), a trueborn son of the European Age of Enlightenment, was celebrated as one of the 112 members of the Eidsvoll Assembly that drew up the Norwegian Constitution in 1814. But he became even more famous as an educator. Grøgaard was the author of two well-known and widely used schoolbooks: an ABC, published in 1815, and a reader, published in 1816. The books were based on the daily life of children, emphasizing understanding more than verbal expression. In this article, his educational ideas are analyzed in a German–Danish–Norwegian as well as a regional context. The article emphasizes the influence that he may have gained during his academic years in Copenhagen 1781–84, and while he served as an auxiliary priest in Zealand 1796–97. In order to understand the regional context that Grøgaard worked within, the school system and the educational situation in Southern Norway around 1800 is also analyzed. Furthermore, the article discusses his ideas on how to improve the education of children, as well as how his schoolbooks were received and evaluated.